Production of biodiesel from castor oil : a feasibility study - Marwah Noori, Mohammed (2013)
In this work, the requirements of a biodiesel plant and the strategic issues to be considered to assess its feasibility. This analysis is useful either when starting a new business, or identifying new opportunities for an existing business. Therefore, it will be extremely helpful for taking rational decisions about the development of a biodiesel production plant. Thus, it is important to understand the transesterification process, and optimize the variables affecting for biodiesel production from castor oil which second generation non edible oil, by acid catalysis (sulphuric and phosphoric acid) and basic catalysis (potassium methoxide and potassium hydroxide). Biodiesel was characterized by a set of parameter according to European Standard, EN 14214. The best conditions for transesterification process were 9:1 methanol/oil molar ratio, 65 ºC, and the use of potassium methoxide as catalyst with concentration 1.0 wt%. The operating cost of the process was estimated using the key information on process operation such as raw materials, utilities, and labor. A profitability analysis was carried out by examining the ROI (Return of Investment) and PP (Payback Period). It was determined that the single most important economic factor is the cost of castor oil. Consequently, a sensitivity analysis was performed to examine the effect of castor oil cost on profitability using the MATLAB code. It was determined that both ROI and PP quickly deteriorate as the cost of castor oil increase. The model bases on using two different sell prices (RM 2.30 and RM 2.60). The ROI is (about 14.48% and 42.05%) and PP is (0.64 and 0.36) respectively. Thus, it can be understood that the models developed in this study are useful tools for estimation of the sensitivity analysis of the biodiesel product from castor oil.